Comparison of outcomes of open reduction and internal fixation versus closed reduction and percutaneous pinning in Song type 4-5 pediatric lateral condyle fractures - Karatas, Muhammed Enes (Turkish Journal of Trauma and Emergency Surgery, 2024)
Lateral condyle fractures are the second most common peri-elbow fractures in children aged 6-10 years, following supracondylar fractures. In treating these fractures, either open or closed reduction fixation can be performed. However, it is not yet completely clear which type of fracture should be treated and how. The Song classification has been increasingly used by orthopedic surgeons for these fractures in recent years. A review of the literature reveals few studies comparing closed reduction and percutaneous pinning (CRPP) and open reduction and internal fixation (ORIF) in lateral condyle fractures (LCFs) with displacements of 2 mm or more. Based on this, we compared Song stage 4 and 5 fractures operated with open or closed reduction methods in our clinic in terms of radiological and clinical aspects. Patients who underwent surgery in our clinic for Song type 4 and 5 lateral condyle fractures between 2011 and 2016 were included in the study. After obtaining approval from our ethics committee (ID: 00171379117), we retrospectively evaluated the medical records of the patients. Between 2011 and 2016, 213 patients underwent surgery for LCF in our hospital, 24 patients were lost to follow-up, and 78 patients had other types of Song fractures. Our study evaluated 111 patients, who were divided into two groups: the CRPP group and the ORIF group. A total of 111 patients were included in our study, with 52 undergoing CRPP and 59 undergoing ORIF. There was no difference between the groups in terms of age, gender, side of injury, mechanism of trauma, and follow-up time (p=0.962, p=0.198, p=0.706, p=0.526, p=1.000, p=0.708, respectively). There was also no significant difference in the displacement amounts between the patients (p=0.233). In the postoperative radiological comparison, a lateral spur was observed in 12 patients (23%) in the CRPP group and 28 patients (47.5%) in the ORIF group. Hardacre's criteria were evaluated as excellent in 46 (88.4%) of the patients who underwent CRPP and 50 (84.7%) of the patients who underwent ORIF. No significant result was found between both groups (p=0.769). There was no difference in complications between the groups (p=1.000). This study demonstrates that in pediatric patients with lateral condyle fractures displaced by 2 mm or more, the choice between open or closed reduction has minimal impact on medium and long-term outcomes. Since there are not many studies on this subject in the literature, we believe that our results will provide valuable guidance for treatment decisions.